Improving Motor Proficiency in Children with Developmental Delays: A Meta-Analysis Evaluating the Impact of Motor Skills Interventions - Siddiqui, Maha; Farooqui, Sumaira Imran; Rizvi, Jaza; Soomro, Bashir Ahmed; Hassan, Batool (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
This study investigated the impact of motor skill interventions in improving motor proficiency among children with developmental delays following Preferred Reporting Items for Systematic Reviews and Meta-analysis “PRISMA” recommendations. The included studies were searched on four databases: Google Scholar, PEDro, MEDLINE, and Cochrane Library. Studies published during the year 2012 to 2022 were selected. The data was extracted by defining the publication year, type of study design, targeted population, and type of physical therapy intervention. The outcome measures included four components of motor proficiency: bilateral coordination, balance, speed and agility, and strength. The results revealed statistically significant findings and a large effect size for bilateral coordination (SMD=1.003, CI=95%) and speed and agility (SMD=0.854, CI=95%). However, a smaller effect size with significant findings was observed in the balance domains (SMD=0.333, CI=95%) and strength (SMD=0.337, CI=95%). Despite the promising results of the analyzed interventions, some of the included studies observed a high risk of bias. However, it is evident from the analysis that protocols directed toward advanced approaches have shown more promising results than traditional physical exercise regimens.